A Provisional Checklist of Orchidaceae of Gunung Halimun-Salak National Park - Wati, Richa Kusuma; Yudistira, Yuda Rehata; Wibowo, Aninda R.U.; S Ma'mun (Buletin Kebun Raya, 2024)
A provisional checklist of Orchidaceae of Gunung Halimun Salak National Park, West Java is present in this study. The checklist includes 328 species belonging to 93 genera. The most representative genera are Bulbophyllum (42 spp.), followed by Dendrobium (27 spp.), Coelogyne (24 spp.), and Appendicula (13 spp.). Of the recorded species from Gunung Halimun-Salak National Park, two species are endangered based on the IUCN redlist, Calanthe ecallosa J.J.Sm. and Paphiopedilum javanicum (Reinw. Ex Blume) Pfitzer. This provisional checklist can be changed with more additional findings on the species. We hope that with the checklist, more people will contribute new observations to update the current information on orchid biodiversity in Gunung Halimun-Salak National Park.